RANCANGAN TEKNOLOGI ASISTIF BAGI SISWA BERKEBUTUHAN KHUSUS DALAM PEMBELAJARAN - Muhammad Nurrohman Jauhari; Sambira Mambela; Ana Rafikayati; Aulia Dwi Shanty; Immanuel Arya Afdyanto; Alya Adjeng Kartikasari (Kanigara, 2024)
The implementation of this community service aims for teachers to provide knowledge, understanding and design assistive technology for students with special needs in learning. The implementation method is a). planning, b). implementation and c). evaluation. Based on the results of the implementation of community service, it can be concluded that training in assistive technology design for students with special needs in learning has a good impact on teachers. The success of increasing participant knowledge is indicated by the average value of the pre-test results of 59.55 increasing to 83.25 in the average value of the post-test.